Influence of Administrative Practices on Students’ Academic Performance in Public Secondary Schools in Matungulu Sub - County, Kenya - Kieti, John Mbithi; Maithya, Redempta; Mulwa, David M. (International Journal of Education and Research, 2017)
The study sought to establish the influence of administrative practices on students’ academic performance in secondary schools in Matungulu Sub-county, Kenya. The study employed descriptive survey research design. Simple random sampling technique was used to select the 230 participating students and 40 teachers in 10 public secondary schools in Matungulu sub-county. All the Principals (10) from all the 10 participating schools were purposively sampled. Three sets of instruments were used to collect data. These included the Students’ Questionnaire (SQ); the Teachers’ Questionnaire (TQ) and the Principals’ Questionnaire (PQ). Statistical Package for Social Sciences (SPSS) version 20 was used in data analysis. The findings of the study revealed that the influence of administrative practices on academic performance was strongly positive and significant (r = .844, P≤ 0.5). The study recommends among others that school principals should intensify the routine checking of professional records by teachers to ensure adherence to the dictates of the professional records.
Keywords: Administrative practices,; students; Academic performance.